Traditional knowledge about polar bear in Chukotka - Zdor, Eduard (Études/Inuit/Studies)

(untitled) (Association Inuksiutiit Katimajiit Inc., 2007)
AbstractThis research note describes a study undertaken from 2004 to 2007 with the aim to create a written collection of Indigenous narratives and traditional knowledge about the polar bear’s role in the cultural, spiritual, and material life of the peoples of Chukotka.